2017
DOI: 10.1002/oby.22030
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peroxisome Proliferator‐Activated Receptor (PPARγ) in Metabolic Disorders in SGA with Catch‐Up Growth

Abstract: Objective: Abnormal fat metabolism is a major disorder in adults who were small for gestational age (SGA). Peroxisome proliferator-activated receptor (PPARc) participates in adipocyte differentiation and the regulation of lipid metabolism. This study explored the role of PPARc in the regulation of fat catch-up growth (CUG) and the lipid metabolism of SGA individuals. Methods: The CUG-SGA rats were treated with pioglitazone. The weight of the visceral adipose tissue, serum lipid levels, and PPARc expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Additionally, PGC-1α is also a coactivator of various transcription factors expressed in skeletal muscle, including PPARγ [ 27 ]. Lian et al have reported that SGA individuals may exhibit high PPARγ expression, which may lead to abnormal fatty acidosis and lipid metabolism disorders [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PGC-1α is also a coactivator of various transcription factors expressed in skeletal muscle, including PPARγ [ 27 ]. Lian et al have reported that SGA individuals may exhibit high PPARγ expression, which may lead to abnormal fatty acidosis and lipid metabolism disorders [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and length were measured weekly. CUG-SGA rats were identified when the body weight and body length were –2 SD higher than those in the control group at 4 weeks of age ( 11 , 20 , 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Children born SGA with CUG have been reported to have fat accumulation, abnormal adipocyte function, and development of adipose tissue caused by adverse intrauterine growth ( 8 , 9 ). Excess fat accumulation can lead to free fatty acid (FFA) release, and high concentrations of FFA can induce insulin resistance in the muscle and liver ( 10 , 11 ). Thus, to develop strategies to prevent insulin resistance, it is crucial to understand the relative contribution of CUG to the emergence of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-γ is fundamental in adipogenesis and adipocyte differentiation, accumulating several functions [ 7 , 9 , 10 ]. This receptor is involved in the process of lipid signaling, which allows lipids to be transported from metabolic organs, including the liver and skeletal muscle, to white adipose tissue (WAT) [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it modulates the expression of adipokines to promote adipocyte differentiation, specifically by increasing the expression of adiponectin and decreasing leptin expression [ 7 , 10 , 11 ]. Furthermore, this transcription factor is involved in cholesterol and triglyceride plasma regulation, which indirectly relates to cardiovascular comorbidities such as atherogenesis and coronary heart disease [ 9 ]. Additionally, PPAR-γ regulates the inflammation observed in WAT, not only by polarizing M1 macrophages, but also by reducing the concentration of these cell types [ 7 ].…”
Section: Introductionmentioning
confidence: 99%